Analisis Faktor-Faktor Yang Berpengaruh Terhadap Kinerja Pegawai Badan Pengelolaan Keuangan Daerah Propinsi Sulawesi Selatan - Hasmawati Hasmawati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
The aim of this research is to know and analysing of the influence of working motivation, working environment and working culture, towards the staffs’ performance of financial management South celebest province and dominant factors analysis which influencing towards staffs performance. This research is caaried out at local financial management in South Celebes Province by utilizing 90 person as respondents. The data analysis used is a descriptive method by explaining the respondents chracteristics and variable description of research. Thus, the quatitave data analysis use multiple regression analysis throught the SPSS program for knowing the working motivation, working environment, working culture as the influence factors towards the staffs’ performance whether simultanious or parcial. The result of this research shows that the simultanious whole independent varables observed positively influence the staffs’s performance of local finacial management Board in the south celebes Province. It seems that the dominant factor influence the staffs’ performabnce is the working environment. Based on the result of this research, it is recommendated to improve the staffs’ performance of local financial management board of South celebes Province needs working motivation, working environment and working culture